CONCEPTUAL PRINCIPLES OF CAPITAL MANAGEMENT IN THE SYSTEM OF ENSURING THE STABILITY OF BANKS - BUHEL, Yuliia (Herald of Khmelnytskyi National University. Economic sciences, 2024)
The article examines the problems of managing banks and the country’s banking system. Attention is focused on the issues of ensuring the financial stability of banks by means of effective and rational management of the capital of banking structures in Ukraine. The purpose of the study is to further develop the conceptual principles and provisions of capital management in the system of ensuring the stability of banks. The theoretical and methodological foundations of the stability of the banking system are summarized on the example of Ukraine. The position of the economic essence and significance of the stability of the banking system is characterized. Banking risks and their impact on the stability of the banking system are outlined. The methodical and applied provisions of managing the stability of the banking system of the state and banks in particular are highlighted. It has been proven that the financial stability of banks should be understood as their ability to withstand macroeconomic factors, fulfill obligations on time, ensure reliability and repayment of funds deposited by individuals and legal entities. It is shown that the biggest threat to the financial stability of the banking system is systemic risks (political, legal, social and general economic), which are formed as a result of changes in the strategic priorities of the socio-economic development of the state, an imperfectly formed organizational and economic mechanism, the inadequacy of the use of operational-tactical methods, means and measures of regulation of socio-economic processes and relations, which affects on the change of the political, social, demographic and economic situation. It has been established that an effective way to reduce systemic risk is the simultaneous consideration of its three main forms: spread risk; the risk of macroeconomic shocks; risk of imbalance.